"تحسين أداء شبكات الحساسات اللاسلكية الثابتة المنشورة عشوائيا في كشف وملاحقة الهدف" (Latakia University Journal -Engineering Sciences Series, 2016)
The tracking using wireless sensor networks is one of the applications that are experiencing significant growth. Due to considerations of wireless sensor networks in terms of limited energy source, researches continue to improve methods of routing and transforming information to ensure lower power. Therefore, we have in this research improved the routing of target location information within WSN by providing a new algorithm, which takes advantage of the concept of clustering for wireless network sensors, with the addition of the possibility of interaction between field sensors that belong to different clusters, where in other cases, they cannot interact with each other in the traditional case of cluster networks. to get rid of repeating the same information transfer, we depend on the parameter intensity of the received signal from the target in the sensors, which will reflect positively on the network age, and give a more accurate indication of the target site. We have implemented the proposed algorithm and showed the results of using the simulator OPNET which is one of the best simulators in the field of various types of networks.يعد التعقب باستخدام شبكات الحساسات اللاسلكية من التطبيقات التي تشهد نمواً كبيراً. ونظرا لمحدودية شبكات الحساسات اللاسلكية من حيث مصدر الطاقة، تستمر الأبحاث لتحسين طرق نقل المعلومات وتوجيهها بما يضمن استهلاكاً أقل للطاقة. لذلك قمنا في هذا البحث بتحسين طريقة توجيه معلومات موقع الهدف في الشبكة وذلك بتقديم خوارزمية جديدة، تستفيد من مفهوم العنقدة في شبكة الحساسات اللاسلكية، مع إضافة إمكانية التفاعل ما بين الحساسات الحقلية التي تنتمي لعناقيد مختلفة، حيث لا يمكن التفاعل فيما بينها في الحالة التقليدية لعمل الشبكات العنقودية، وذلك اعتماداً على بارامتر شدة الإشارة المستقبلة من الهدف في الحساسات لغاية التخلص من تكرار نقل نفس المعلومة، مما ينعكس إيجاباً على عمر الشبكة والحصول أيضاً على إشارة أكثر دقة لموقع الهدف. قمنا بتطبيق الخوارزمية المقترحة وإظهار نتائجها باستخدام محاكي OPNET الذي يعد من أفضل المحاكيات في مجال الشبكات بأنواعها المختلفة.